The impact of gum-chewing on postoperative ileus following gynecological cancer surgery: A systematic review and meta-analysis of randomized controlled trials - Yin, Ya-Nan; Xie, Hong; Ren, Jian-Hua; Jiang, Ni-Jie; Dai, Li (Frontiers in Oncology, 2023)
Objective To assess the effect and safety of gum-chewing on the prevention of postoperative ileus after gynecological cancer surgery. Methods We conducted a systematic review of randomized controlled trials (RCTs) published between 2000 and 2022 in English and Chinese, using the EBSCO, Web of Science, Scopus, Cochrane Central Register of Controlled Trials (Cochrane database), PubMed, Medline (via Ovid), Chinese National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database, and Wan Fang databases. A total of 837 studies were screened using Endnote software, and those that met the inclusion criteria were selected for analysis. The main outcome of interest was the incidence of postoperative ileus, and secondary outcomes included time to first flatus, time to first bowel movement, and length of hospital stay. Results Two authors extracted data and performed quality assessment independently. The review included six RCTs with a total of 669 patients. Compared with routine care, gum-chewing could significantly reduce the incidence of postoperative ileus (RR 0.46, 95% CI: 0.30, 0.72, P=0.0006), shorten the time to first flatus (WMD -9.58, 95% CI: -15.04, -4.12, P=0.0006), first bowel movement (WMD -11.31, 95% CI: -21.05, -1.56, P=0.02), and the length of hospital stay (WMD -1.53, 95% CI: -2.08, -0.98, P<0.00001). Conclusions Gum-chewing is associated with early recovery of gastrointestinal function after gynecological cancer surgery and may be an effective and harmless intervention to prevent postoperative ileus. Systemaic review registration https://www.crd.york.ac.uk/prospero/#searchadvanced, identifier CRD42022384346.